Literasi Keuangan Dan Resiliensi Keuangan Mahasiswa: Ditinjau Dari Perspektif Gender - Nyoman Trisna Herawati; Luh Gede Kusuma Dewi; Made Ary Meitriana (KRISNA: Kumpulan Riset Akuntansi, 2024)
Nowadays, students are very active in using financial technology as a means of payment or investment. For this reason, good financial literacy and resilience are needed to maintain financial well-being in the future. This study aims to examine financial literacy and financial resilience in Accounting Study Program students from a gender perspective. The research method used a quantitative descriptive approach. A total of 156 active students of Universitas Pendidikan Ganesha became respondents. Data were collected using a financial literacy test and a financial resilience questionnaire. The results showed that the average level of financial literacy was moderate. Viewed from a gender perspective, the average financial literacy of women (M=9,36) is higher than that of men (M=9,31). However, the average financial resilience of men (M=50,72) is higher than that of women (M=50,15). Based on financial literacy indicators, men have a better understanding of the concepts of investment and insurance. Meanwhile, women have a better understanding of basic financial concepts and credit management. Based on financial resilience indicators, men have a better ability to control money, the ability to manage financial stress, and have financial planning. Women are able to watch their spending and have a better financial cushion. Financial literacy is positively correlated to financial resilience with a correlation value of 0,134 (p=0,047). These results indicate that there is a significant relationship between financial literacy and financial resilience. The higher a person's financial literacy will increase their financial resilience.